Bioactive insectistatic compounds from Solanaceae against Zabrotes subfasciatus (Boheman) (Coleoptera: Chrysomelidae: Bruchinae) - Gonçalves, Gabriel Luiz Padoan (2018)
Plants produce a wide range of insectistatic phytochemicals for protection against the damages caused by phytophagous insects. They can harm insect eggs, nymphs, larvae and adults promoting mortality, repellency, phagodeterrence, morphological deformations, prolongation of development, reduce nutrient-intake etc. Plant bioactive compounds have been used to control insect pests in agriculture since ancient times, but during Green Revolution many of them were replaced by synthetic compounds such as organochlorines, organophosphates, carbamates and pyrethroids. Nonetheless, the excessive and irrational use of synthetic insecticides in agriculture led to environmental and health issues and the selection of resistant insect pest populations. As a response to these negative aspects of synhtetic insecticides, it was developed stringent regulatory laws and requirements for pesticide registration at Governmental Regulatory Agencies resulting in higher costs to develop new commercial synthetic insecticides. Inevitably, scientific studies with bioprospection of insectistatic compounds from plants have grown in order to discover safer insecticides with new modes of action. Therefore, in the present study, it was performed a screening with 25 ethanolic extracts from 17 Solanaceae species in order to evaluate their bioacticity against the Mexican bean weevil, Zabrotes subfasciatus (Boheman, 1833) (Coleoptera: Chrysomelidae: Bruchinae). Ethanolic extracts from leaves of Solanum lycocarpum A. St.-Hil and flowers of Brugmansia suaveolens (Willd.) Bercht. & J.Presl were the best ones; thereby they were selected for bioguided fractionations (Solid Phase Extraction) based on toxicological bioassays in order to identify their bioactive compounds. The chemical fractions from S. lycocarpum killed adults of Z. subfasciatus, reduced the number of eggs per sample (due to oviposition deterrence and the decrease of fecundity), and reduce F1 progeny and damages on bean grains, and also reduced the fecundity of F1 progeny. The observed bioacticity promoted by fractions of S. lycocarpum is possibly due to the presence of whitanolides and alkaloids. On the other hand, bioactive fractions from B. suaveolens promoted an intense reduction on egg-adult viability preventing the embryonic development in Z. subfasciatus eggs. Consequently, F1 progeny and damages on bean grains were completely inhibited as well. Moreover, they also killed adults of Z. subfasciatus, which demonstrated signs of hyperexcitation, a symptom related to neurotoxic insecticides. It was identified fatty acid derivatives in the bioactive fraction BSHidAcF1-1-C through a Gas Chromatography Mass Spectrometry analysis. The results acquired in the present study demonstrate the potential of prospecting insectistatic compounds in Solanaceae species in order to protect bean grains against the damages promoted by Z. subfasciatus in warehouses.